2019
DOI: 10.3390/en12203992
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Sub-Critical Choke Flow Performance in High Rate Gas Condensate Wells

Abstract: There have been some correlations in the literature to predict the gas and liquid flow rate through wellhead chokes under subcritical flow conditions. The majority of these empirical correlations have been developed based on limited production data sets that were collected from a small number of fields. Therefore, these correlations are valid within the parameter variation ranges of those fields. If such correlations are used elsewhere for the prediction of the subcritical choke flow performance of the other f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…They adapted the Gilbert equation in three modified forms by changing the pressure parameters (replacing the upstream pressure with the pressure drop across the choke) for the wells' data in gas condensate reservoirs. [30]. Seidi and Sayahi (2015), by adapting Gilbert's basic equation using the genetic algorithm and nonlinear regression methods and applying them to 67 datasets gathered from different gas condensate fields, proposed an optimized model for estimating the condensate gas flow rate [31].…”
Section: Introductionmentioning
confidence: 99%
“…They adapted the Gilbert equation in three modified forms by changing the pressure parameters (replacing the upstream pressure with the pressure drop across the choke) for the wells' data in gas condensate reservoirs. [30]. Seidi and Sayahi (2015), by adapting Gilbert's basic equation using the genetic algorithm and nonlinear regression methods and applying them to 67 datasets gathered from different gas condensate fields, proposed an optimized model for estimating the condensate gas flow rate [31].…”
Section: Introductionmentioning
confidence: 99%
“…While most studies considered three input parameters (wellhead pressure, choke size and GOR), others included parameters such as water cut, BS&W, API gravity and gas liquid ratio. The widest range of wellhead temperature was in the study by Nasriani et al (2019) wherein the temperature ranges from 191 to 463 • F, while the least range was 60-120 • F as given by Abdul-Majeed (1988). For all wellhead pressure ranges, the highest [1400-12000 psia] was that given by , while the least [60-350 psia] was by Ganat and Hrairi (2018).…”
Section: Parameter Ranges Used In Empirical Models For Oil and Gas Fl...mentioning
confidence: 91%
“…Ganat and Hrairi (2018) Non-linear regression The developed model is quick, reliable, and can be adapted to any ESP oil well as well as artificially onshore and offshore flowing wells but can only be applied to critical flow conditions. Fuladgar and Vatani (2019) Multi variable linear regression An evaluation of the new correlation indicated that it could significantly improve accuracy of flowrate predictions in contrast to previous prominent correlations Nasriani et al (2019) Non-linear regression This model works best when applied within the range of the following production parameters: LGR of 0.7-178.8 bbl/MMscf, a choke size: 24/64 to 192/64, gas flow rate of 5.4-113.3 MMscfD. intelligence, a seamless merger of two or more machine learning techniques with the aim of complementing each other is called hybrid computational intelligence or hybrid intelligent systems (Anifowose, 2011).…”
Section: Zangl Et Al (2014) Linear Regression Ann Random Forest Class...mentioning
confidence: 97%
See 1 more Smart Citation